Diagnosis of hypertension: Ambulatory pediatric American Heart Association/European Society of Hypertension versus blood pressure load thresholds. Issue 11 (20th October 2021) - Sharma, Ajay P.; Altamirano‐Diaz, Luis; Mohamed Ali, Mohamed; Stronks, Katryna; Kirpalani, Amrit; Filler, Guido; Norozi, Kambiz
Abstract: The agreement between the traditionally‐used ambulatory blood pressure (ABP)‐load thresholds in children and recently‐recommended pediatric American Heart Association (AHA)/European Society of Hypertension (ESH) ABP thresholds for diagnosing ambulatory hypertension (AH), white coat hypertension (WCH), and masked hypertension (MH) has not been evaluated. In this cross‐sectional study on 450 outpatient participants, the authors evaluated the agreement between previously used ABP‐load 25%, 30%, 40%, 50% thresholds and the AHA/ESH thresholds for diagnosing AH, WCH, and MH. The American Academy of Pediatrics thresholds were used to diagnose office hypertension. The AHA threshold diagnosed ambulatory normotension/hypertension closest to ABP load 50% in 88% (95% CI 0.79, 0.96) participants (k 0.67, 95% CI 0.59, 0.75) and the ESH threshold diagnosed ambulatory normotension/hypertension closest to ABP load 40% in 86% (95% CI 0.77, 0.94) participants (k 0.66, 95% CI 0.59, 0.74). In contrast, the AHA/ESH thresholds had a relatively weaker agreement with ABP load 25%/30%. Therefore, the diagnosis of AH was closest between the AHA threshold and ABP load 50% (difference 3%, 95% CI ‐2.6%, 8.6%, p  = .29) and between the ESH threshold and ABP load 40% (difference 4%, 95% CI ‐2.1%, 10.1%, p  = .19) than between the AHA/ESH and ABP load 25%/30% thresholds. A similar agreement pattern persisted between the AHA/ESH and various ABP load thresholds for diagnosing WCH and MH. The AHA and ESH thresholds diagnosed AH, WCH, and MH closest to ABP load 40%/50% than ABP load 25%/30%. Future outcome‐based studies are needed to guide the optimal use of these ABP thresholds in clinical practice.